Effect of chlorhexidine incorporation on the surface properties of acrylic reline resins - Barreiros, Marta Cristina Silvério (2016)
Tese de Mestrado, Medicina Dentária, Universidade de Lisboa, Faculdade de Medicina Dentária, 2015